A study of moderately underexpanded single and twinjet rocket exhaust plumes in quiescent and in a mach 7 hypersonic freestream - Shek, H; Shek, Howard (1997)
﻿Rocket plume flowfields have an importance due to their influence on the signature of the rocket and also on the distribution of the plume gases around the vehicle. Little information on the co-flowing situation exists other than a previous study at Oxford. This thesis thus represents a significant database for co-flowing rocket plumes of this form. The work presented deals with two new aspects of co- flowing rocket plumes in that detailed flowfield measurements have been made and plumes from twin nozzle have been investigated for the first time in this thesis. This study on twinjet rocket plumes was carried out using the University of Oxford Gun Tunnel. Twinjet rockets with nozzle exit Mach numbers of 3 and 5 were tested in quiescent and in co-flow at Mach 7 using nitrogen and hydrogen injections. A major feature of the twinjet case was the so-called impingement shock between the flows from the two nozzles. It was discovered that this shock was insensitive to the freestream and scaling parameters are suggested for its geometry. Comparisons with single equivalent thrust nozzles are made at downstream locations and similar Pitot pressure profiles were observed for nitrogen injection in a nitrogen freestream after approximately 3 nozzle diameters downstream. Shear layers were studied and fluctuations in this region were measured by fast-response Pitot pressure and heat transfer probes sampled at 1.1 MHz. The extent of the shear layer was deduced using a new Oxford Total Temperature Probe. With the freestream stagnation temperature at approximately 650 K and injected gas at 350 K, a linear variation for the deduced total temperature across the shear layer was obtained. This was consistent with the Pitot pressure variations across this region. Convective heat transfer coefficient fluctuations and flow total temperature fluctuations across rocket flowiields were obtained using three thin-film heat transfer probes and found to be closely correlated. Experimental results for the twinjet and the single jet were compared with CFD simulations and good overall agreements were achieved. Instrumentation for the hypersonic experiments was investigated and a fast-response (~ 20 kHz) Pitot probe suited for flows heavily contaminated with particulate was developed and tested.